Regulation of ICAM‐1 expression in gingival fibroblasts infected with high‐glucose‐treated P. gingivalis. (29th April 2013) - Chang, Li‐Ching; Kuo, Hsing‐Chun; Chang, Shun‐Fu; Chen, Heng Jung; Lee, Kam‐Fai; Lin, Tseng‐Hsi; Huang, Ting‐Ying; Choe, Chu‐Shan; Lin, Li‐Tsen; Chen, Cheng‐Nan
Summary Porphyromonas gingivalis is a major pathogen in the initiation and progression of periodontal disease, which is recognized as a common complication of diabetes. ICAM‐1 expression by human gingival fibroblasts (HGFs) is crucial for regulating local inflammatory responses in inflamed periodontal tissues. However, the effect of P. gingivalis in a high‐glucose situation in regulating HGF function is not understood. The P. gingivalis strain CCUG25226 was used to study the mechanisms underlying the modulation of HGF ICAM‐1 expression by invasion of high‐glucose‐treated P. gingivalis (HGPg). A high‐glucose condition upregulated fimA mRNA expression in P. gingivalis and increased its invasion ability in HGFs. HGF invasion with HGPg induced increases in the expression of ICAM‐1. By using specific inhibitors and short hairpin RNA (shRNA), we have demonstrated that the activation of p38 MAPK and Akt pathways is critical for HGPg‐induced ICAM‐1 expression. Luciferase reporters and chromatin immunoprecipitation assays suggest that HGPg invasion increases NF‐κB‐ and Sp1‐DNA‐binding activities in HGFs. Inhibition of NF‐κB and Sp1 activations blocked the HGPg‐induced ICAM‐1 promoter activity and expression. The effect of HGPg on HGF signalling and ICAM‐1 expression is mediated by CXC chemokine receptor 4 (CXCR4). Our findings identify the molecular pathways underlying HGPg‐dependent ICAM‐1 expression in HGFs, providing insight into the effect of P. gingivalis invasion in HGFs.